High Resolution Mapping of a Hordeum bulbosum-Derived Powdery Mildew Resistance Locus in Barley Using Distinct Homologous Introgression Lines - Hoseinzadeh, Parastoo; Ruge-Wehling, Brigitte; Schweizer, Patrick; Stein, Nils; Pidon, Hélène (Frontiers in Plant Science, 2020)
Powdery mildew caused by Blumeria graminis f.sp. hordei (Bgh) is one of the main foliar diseases in barley (Hordeum vulgare L.; Hv). Naturally occurring resistance genes used in barley breeding are a cost effective and environmentally sustainable strategy to minimize the impact of pathogens, however, the primary gene pool of H. vulgare contains limited diversity owing to recent domestication bottlenecks. To ensure durable resistance against this pathogen, more genes are required that could be unraveled by investigation of secondary barley gene-pool. A large set of Hordeum bulbosum (Hb) introgression lines (ILs) harboring a diverse set of desirable resistance traits have been developed and are being routinely used as source of novel diversity in gene mapping studies. Nevertheless, this strategy is often compromised by a lack of recombination between the introgressed fragment and the orthologous chromosome of the barley genome. In this study, we fine-mapped a Hb gene conferring resistance to barley powdery mildew. The initial genotyping of two Hb ILs mapping populations with differently sized 2HS introgressions revealed severely reduced interspecific recombination in the region of the introgressed segment, preventing precise localization of the gene. To overcome this difficulty, we developed an alternative strategy, exploiting intraspecific recombination by crossing two Hv/Hb ILs with collinear Hb introgressions, one of which carries a powdery mildew resistance gene, while the other doesn't. The intraspecific recombination rate in the Hb-introgressed fragment of 2HS was approximately 20 times higher than it was in the initial simple ILs mapping populations. Using high-throughput genotyping-by-sequencing (GBS), we allocated the resistance gene to a 1.4 Mb interval, based on an estimate using the Hv genome as reference, in populations of only 103 and 146 individuals respectively, similar to what is expected at this locus in barley. The most likely candidate resistance gene within this interval is part of the coiled-coil nucleotide-binding-site leucine-rich-repeat (CC-NBS-LLR) gene family, which is over-represented among genes conferring strong dominant resistance to pathogens. The reported strategy can be applied as a general strategic approach for identifying genes underlying traits of interest in crop wild relatives.